PENGARUH PERPUTARAN KAS, PERPUTARAN PIUTANG DAN PERPUTARAN PERSEDIAAN TERHADAP RENTABILITAS EKONOMI PADA KPRI DI KABUPATEN GUNUNGKIDUL PERIODE TAHUN 2014-2016 - Eva Listiyana (JURNAL EKOBIS DEWANTARA, 2018)
The purpose of this research is to analyze the impact of cash turnover, receivable turnover and inventory turnover simultaneously and partially to economic rentability of KPRI in Gunungkidul Regency 2014-2016 period. The nature of research is correlational. The population is 36 KPRI in Gunungkidul Regency with sampling method that is used in research is purposive judgment sampling. The samples are KPRI Bangun, KPRI Anggun, KPRI Tegak, KPRI Agung, KPRI Makmur, KPRI Dame, KPRI Kejari, KPRI Meter, KPRI Bangun, KPRI Karya Manunggal. The data is obtained by documenting data. Techniques analyse using multiple regression analysis supported by the classical assumption test that is normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. The results showed that effect of cash turnover, receivables turnover and inventory turnover simultaneously on economic profitability obtained significant results with a significance value of 0.000 <0.05. Partially, with T test showed that cash turnover, receivable turnover and inventory turnover also get significant result to economic profitability with value of cash turnover 0,001 <0,05, receivable turnover 0,028 <0,05 and inventory turnover 0,000 <0,05